Infectious spondylodiscitis treated at the Department of Infectious Diseases, Cantonal Hospital Zenica, during the period from 2022 to 2023 - Eldira Hadzic; Meliha Šehić; Rasim Skomorac; Nadira Zahirovic; Mile Bosilkovski (Medicinski glasnik, 2026)
Aim: Infectious spondylodiscitis is a rare but serious spinal infection that often presents with nonspecific symptoms like fever and back pain, causing delayed diagnosis. This study aimed to describe clinical features, identify etiological agents, and outline treatment approache in patients treated at the Department of Infectious Diseases, Cantonal Hospital Zenica, Bosnia and Herzegovina, from January 2022 to December 2023. Methods: This retrospective descriptive study included 60 patients diagnosed with infectious spondylodiscitis based on clinical symptoms (fever and/or spinal pain) and confirmed by magnetic resonance imaging (MRI) or scintigraphy. Data were collected from medical records and included demographic information, clinical presentation, laboratory results: hemoglobin, leukocytes, C-reactive protein (CRP), liver enzymes), microbiological findings (blood cultures and serology), imaging, and treatment details. Results: Median time from symptom onset to hospital admission was 30 days. Blood culture was positive in 31 (51.6%) patients, while etiology was identified in 57 (95%) cases. Brucella species was the most common pathogen, confirmed serologically in 46 (90.2%) of brucella cases. Most patients had a history of unpasteurized dairy consumption or animal contact. The MRI was performed in 58 (96.7%) of patients, confirming vertebral inflammation. Complications such as abscesses, epidural collections, or empyema occurred in 35 (58.3%) patients. Conclusion: Due to its nonspecific presentation, infectious spondylodiscitis is often diagnosed late. In endemic regions, brucellosis should be considered as a potential cause. Blood cultures and serology are key for etiological confirmation, while MRI remains the diagnostic gold standard. Targeted antimicrobial therapy is the mainstay of treatment, with surgery indicated in complicated cases.
Keywords: Vertebral osteomyelitis; brucellosis; antibiotics; magnetic resonance imaging (MRI)